Adobe Flash-based Edutainment Media: is it suitable for learning math? - Indah Sari, Tri Hariyati Nur Indah Sari; Lestari, Wiwit Damayanti (JDIME: Journal of Development and Innovation in Mathematics Education, 2023)
Since information and communication technology (ICT) is developing so fast in today's digital era, it is important to create learning materials that can be accessed through various digital devices. The purpose of this research is to create edutainment media that can be applied for arithmetic learning. This research uses the Borg and Gall (R&D) development model which is limited to several stages. These stages are: a) information gathering; b) planning; c) product manufacturing; and d) validation and testing. The questionnaire was the research instrument. A total of 34 students who were the test subjects as well as material and media validators were sent questionnaires. Descriptive quantitative analysis was used for data analysis. Validation of Adobe Flash-based math learning media by material experts resulted in an overall score of 78.7%, including the criteria of "Eligible". Based on the results of media expert validation, the "Appropriate" criteria were met with a percentage of 76.54% of the total score. In line with the findings from student responses, the overall score is 81.21%, which is in the "Very Feasible" criteria. Based on the results of this study, Adobe Flash is an alternative that can be used to create entertaining learning media for mathematics education.